A comparative study between outbred and inbred rat strains for the use in in vivo IPV potency testing. Issue 21 (17th May 2018) - Bockstal, Viki; Sanders, Barbara; Achterberg, Rogier; Tiemessen, Machteld; Bogaert, Lies; Van der Meer, Marjolein; Schuitemaker, Hanneke; Zahn, Roland
Highlights: Different rat strains respond differently to IPV immunization. IPV immunogenicity differs substantially between outbred and inbred rat strains. The outbred Wistar rat strain is most suited for IPV potency evaluation. Abstract: In vivo potency testing of inactivated poliovirus vaccines (IPV) is generally performed in rats, although no systematic investigation has identified the most appropriate rat strain for anti-poliovirus antibody quantification. We investigated humoral immune responses to IPV in five different rat strains to identify the most suitable strain. Three outbred (Wistar, Wistar Hannover, Sprague-Dawley) and two inbred rat strains (Fisher 344, Wistar Furth) were immunized intramuscularly with a full or one-fifth human dose of commercial IPV. Anti-poliovirus neutralizing antibody (NA) titers were measured using Salk and Sabin virus neutralizing assays. Post-vaccination responses varied between strains; inbred strains showed greater animal-to-animal variation in NA responses than outbred strains. Virus NA titers persisted for 9 weeks with little reduction in the response. The outbred Wistar rat model was identified as the preferred strain for IPV potency testing based on its capacity to produce high, dose-dependent anti-poliovirus NA responses, with low animal-to-animal variation.